Motion and its action in building design (Journal of the College of Basic Education, 2022)
Mourns this research is to study the movement in design movement is here the subject of a contemporary because of their technical interventions and the addition of a creative in the form of productions around us and is the movement one of the most important factors associated with the technical, aesthetic and utilitarian concepts and shows the significant impact of these concepts in society and human movement in his vision of the needs updated with the change of time, and to try to understand the movement in various productions around us to Aigsd including the development of standards for these concepts and identified, or the development of rules for the application to reach a production that characterized the movement and Anmaaltousel to the basic pillars on which this production thus necessary to put the concept of movement in design and clarification , and what are the basic aspects underlying the relationship on both sides, was like that year axis in the first part and the second part, as it represented the problem of public research (b blurred knowledge movement in design and what is their impact on production) where This research aims to put up as part of a knowledge shows the relationship between the two sides and what are the effects resulting from this relationship on the output with the introduction of the final conclusions of the research